Against the Stream: religion and mental health – the case for the inclusion of religion and spirituality into psychiatric care - Dein, Simon (BJPsych Bull, 2018)
This paper argues for the inclusion of religion and spirituality in psychiatric care. After discussing the antagonism of psychiatrists and psychologists to religion, I present a critical overview of studies examining the relationships between spirituality, religion and diverse aspects of mental health: depression, suicide, anxiety, delinquency, drug abuse and schizophrenia. The need to assesses the impact of religion in different faith groups is discussed. Measures of religious coping, both positive and negative, may provide a more accurate portrayal as to how individuals deploy religion in their lives than global measures such as belief and attendance. I highlight the fact that there is a dearth of research on ritual, prayer and other aspects of religious experience. While many studies demonstrate positive effects of religion on mental health, others find detrimental effects. Finally I examine the clinical implications of these findings. DECLARATION OF INTEREST: None.